Towards an Islamic application of visual privacy principles on Malaysian terrace housing: a conceptual framework - Abd Manaf, Azhani; Abdul Rahim, Zaiton; Abdul Majid, Noor Hanita; Omer, Spahic (Malaysian Institute Of Planners, 2018)
This paper proposes a conceptual framework illustrating the application of Muslim Visual Privacy (MVP) of terrace housing by Malay occupants living in urban areas of Malaysia. Malay occupants are central to this study due to their specific views and requirements on visual privacy defined by religion and cultural norms. The study employs a thorough analysis of empirical data and review of past literatures in order to discuss vital and relevant theories. The findings of this study suggested a conceptual framework incorporating the sources of MVP elements as well as other important variables influencing the Malay Muslim occupants in terms of how they apply, regulate and modify the visual privacy levels in their respective terrace houses. The proposed framework might only represent a small portion in the entire effort, nevertheless it remains a significant contribution towards arriving at a more valid definition of MVP for Malay occupants in terrace housing. A clearer definition will then assist architects, developers as well as home owners’ themselves in terms of how they design and manipulate physical elements of the house to achieve more functional visual privacy levels as per religious requirements.